Real-World Experience with CDK4/6 Inhibitors in the First-Line Palliative Setting for HR+/HER2− Advanced Breast Cancer - Ram Patel; John Mathews; Caroline Hamm; Swati Kulkarni; Rasna Gupta; Tarquin Opperman; John Dean Chiong; Abdullah Nasser (Current Oncology)
Introduction: CDK4/6 inhibitors in combination with aromatase inhibitors (AIs) are the standard first-line treatment for hormone receptor-positive (HR+), HER2-negative (HER2−) metastatic breast cancer. Landmark trials have demonstrated a comparable progression-free survival (PFS) across CDK4/6 inhibitors, but the overall survival (OS) outcomes have varied. This study aimed to evaluate the real-world PFS and OS for palbociclib and ribociclib when combined with AIs in patients with HR+/HER2− advanced breast cancer. Materials and Methods: This was a retrospective chart review of adult patients with HR+/HER2− metastatic breast cancer treated at a single academic center between 1 January 2015 and 1 December 2022. The baseline demographics, clinical characteristics, and treatment details were extracted. A Kaplan–Meier analysis was used to estimate the PFS and OS, and differences between the treatment groups were assessed using the log-rank test. Cox proportional hazards models were constructed to adjust for confounding factors. Results: Seventy-five patients were included in the final analysis. The cohort was predominantly female (98.7%) and postmenopausal (77.3%), with 52.0% having de novo stage IV disease. Palbociclib was prescribed to 74.7% of the patients, and ribociclib to 25.3%. The patients receiving ribociclib were significantly younger (57.6 vs. 67.5 years, p = 0.013) and more likely to be premenopausal (42.1% vs. 5.4%, p < 0.001). The real-world median PFS and OS for palbociclib were 20.3 months (95% CI: 14.8–46) and 37.2 months (95% CI: 20.3–not reached [NR]), respectively. For ribociclib, the median PFS and OS were not reached. The Cox proportional hazards models adjusting for age and menopausal status found no significant differences between ribociclib and palbociclib for the PFS (HR = 0.92, p = 0.86) or OS (HR = 0.95, p = 0.92). Conclusion: In this real-world analysis, palbociclib demonstrated a median PFS consistent with the results from landmark trials, although the observed OS was shorter. The ribociclib-treated patients had a numerically longer PFS and OS compared with those treated with palbociclib, but the differences were not statistically significant. The discontinuation rates were similar between the two groups.